PENINGKATAN KECERDASAN VERBAL LINGUISTIK ANAK USIA DINI MELALUI PERMAINAN “GERBONG KATA” - Setyorini, Ririn; Sandi, Noviea Varahdilah; Wibisono, Yusup (Generasi Emas, 2018)
Early childhood is a group of individuals who desperately need education and mentoring that are good for their future. Early childhood has different characteristics with adults, as well as their learning process. Early childhood requires a fun learning process so that the process of learning early childhood does not get bored quickly. Many ways can be done to help children in the learning process. The most fun learning process for early childhood is by playing. Besides they can get useful lessons, through playing early childhood able to socialize well through playing. linguistic verbal intelligence is an intelligence that must be possessed by a child, the increase in verbal linguistics of children must be taught as early as possible so they have good verbal linguistics. There are many ways that can be used to improve the linguistic verbal intelligence of children, one of them is the word carriage game. This game is very easy and inexpensive, besides it can be used anywhere, this game can be played by anyone and certainly can improve verbal linguistics of early childhood.